Powerful knowledge and the textbook (UCL Press, 2018)
This article draws on experience both within commercial textbook publishing and on textbook-development projects at the UCL Institute of Education to interrogate the current dynamics of 'neoliberal' edu-business (after Ball, 2012). The author discusses some damaging limitations inherent in publishing coursebooks predicated on what Young and Muller (2010) term a 'Future 2' approach, and outlines the potential benefits of classroom materials that allow 'knowledge' and 'text' back in. The discussion is situated mainly in the context of England, where a subject-specialist approach to teaching and learning is strongly advocated in the policy environment.